Identification of RNA-binding proteins in spinal cord injury: an in-silico approach - Idris, Jalilah; Pang, Jyh Chyang; Wan Ahmad Kamil, Wan Nur Ismah; Daud, Muhammad Fauzi (Universiti Putra Malaysia, 2023)
Introduction: Gene expression is regulated by trans-acting factors such as microRNA, and RNA-binding proteins (RBPs). Dysregulation of RNA-binding proteins (RBPs) are found in neurological diseases. However, the role RBPs in spinal cord injury (SCI) have not been identified. The objective of this study was to identify RBPs by re-analyzing RNA-sequencing data from SCI mice model using the latest version of Tuxedo pipeline. Methods: Reads from transcriptomic sequence of acute, subacute, and control mice models, from the Sequence Read Archive (SRA) website, were uploaded to a scientific workflow system called usegalaxy.org. The reads were assessed for their quality using FastQC, before they were mapped to the mouse mm10 reference genome using HISAT2. The fragments were then aligned to full-length transcripts using Stringtie, followed by DESeq2 to find differentially expressed genes (false discovery rate of 0.05 and fold change of -1< x >1). Finally, to find functional annotations, the Protein Analysis through Evolutionary Relationship (PANTHER) and g:Profiler were used. Results: There were 24 RBP-coding genes identified in the acute injury, and 27 in the subacute injury. Four RBPs that were commonly expressed at high levels in both acute and subacute injury; Hnrnpm, Ptbp3, Rbfox3 and Znf385a. These proteins regulate alternative splicing, and RNA transport. Other RBP-coding genes with a role in inflammatory response and apoptosis were also discovered. Conclusion: Novel RBP-coding genes differentially expressed in SCI were discovered, suggesting their role in the pathophysiology of SCI. These findings contribute to a better understanding of the regulatory mechanisms employed by RBPs in SCI.